Energy Decay for the Solutions of a Coupled Wave System - Raposo, C.A.; Bastos, W.D. (Trends in Computational and Applied Mathematics, 2009)
In this work we establish existence, uniqueness and exponential decay of energy for the solutions of a system of wave equations coupled with locally distributed damping in a bounded smooth domain of any space dimension.